Modeling the Morphological Responses of the Yellow River Delta to the Water‐Sediment Regulation Scheme: The Role of Impulsive River Floods and Density‐Driven Flows - Guoxiang Wu; Kemeng Wang; Bingchen Liang; Xiao Wu; Houjie Wang; Huajun Li; Benwei Shi (Water Resources Research)
Abstract Morphological evolution of river deltas depends to a large extent on river discharges, which are usually highly unsteady due to natural hydrological cycles and anthropogenic regulations. However, it is unclear that how and to what extent the discharge fluctuations influence the delta morphology. In this study, we focus on the morphological response of the Yellow River Delta to the Water‐Sediment Regulation Schemes, which generate impulsive floods and deliver high sediment load within a short time. Tracking the fate of fluvial sediment released by 10 historical events reveals that 51.3%, 19.7%, and 17.8% of fluvial sediment are deposited in the delta front, the subaerial delta and the prodelta, respectively. Hypopycnal and hyperpycnal flows occur alternately during different phases of the regulation schemes, and the latter contribute to 32% of the deposition volume with 10% of the duration. To explore the effects of river discharge schematizations on delta evolution, numerical experiments are conducted to compare models forced by unsteady and constant discharges, with the latter being a common practice in delta morphology modeling. We show that the constant‐discharge simplification fails to capture the highly‐depositional hyperpycnal flows, leading to dramatic underestimation of river mouth depositions. In addition, we demonstrate that including the 3D flow‐sediment interactions are critical in reproducing the correct plume structures, bed surface sediment compositions and deposition patterns. Our study highlights the importance of proper river discharge schematizations and full consideration of flow‐sediment interactions in modeling deltas affected by episodic river floods and high suspended sediment concentrations.